Pathophysiological background and prognostic implication of systolic aortic root motion in non-ischemic dilated cardiomyopathy - Aurich, Matthias; Greiner, Sebastian; Müller-Hennessen, Matthias; Uhlmann, Lorenz; Giannitsis, Evangelos; Ehlermann, Philipp; Meder, Benjamin; Katus, Hugo; Mereles, Derliz (Scientific reports, 2019)
Recordings of aortic root movement represent one of the first accomplishments of ultrasound in medicine and mark the beginning of functional cardiac imaging. However, the underlying mechanism is not completely understood. Since the aortic root is directly connected to the cardiac skeleton we hypothesize, that the amplitude of systolic aortic root motion (SARM) may be mainly caused by displacement of the cardiac base towards the apex and might therefore be used as measure of left ventricular longitudinal function (LV-LF). One hundred and eighty patients with dilated cardiomyopathy and 180 healthy controls were prospectively included into this study. SARM was lower in patients compared to controls (9 ± 3 mm vs. 12 ± 2 mm, p < 0.001) and lowest in patients with cardiovascular events (9 ± 3 mm vs. 7 ± 3 mm, p < 0.001). During a median follow-up time of 38 months, the combined end-point of cardiovascular death or hospitalization for heart failure was reached by 25 patients (13.9%). Reduced SARM had significant prognostic impact on outcome (hazard ratio 0.74, 95% confidence interval 0.63-0.88, p < 0.001) and remained an independent predictor in the multivariate analysis. Compared to parameters with potential influence on its mechanism, SARM correlated best (r = 0.75, p < 0.001) with global longitudinal strain (GLS). SARM may therefore represent an alternative echocardiographic parameter for the assessment of LV-LF, particularly when GLS is not feasible or apical views are not available.